Reprocessing of Regional 2D Marine Seismic Data of Part of Taranaki Basin, New Zealand Using Latest Processing Techniques - OSINOWO, Olawale Olakunle (GeoScience Engineering, 2020)
This study employed the use of various newly developed seismic data processing techniques, which had not been available as at the time (1986) of acquisition of the regional 2D marine seismic data (TRV 434) of part of Taranaki Basin, New Zealand, to reprocess the data in order to improve the volume as well as the quality of subsurface information derivable from the data which remain one of the vital sources of information for the preliminary insight for petroleum prospect evaluation of the basin. The reprocessing operations attenuated various unwanted signals associated with the seismic data, F – K transform filter filtered out low frequency noise including swell noise, while other noise types embedded in the seismic data were attenuated using Time Variant Omsby-Bandpass filters. Predictive deconvolution attenuated water bottom multiples as well as other periodic unwanted signals. True amplitude recovery technique restored lost reflection energies and made deeper reflections visible. Post and Pre-Stack Time Kirchhoff migration (PSTM) techniques appropriately repositioned dipping reflection events to their appropriate locations in time and space. Diffraction curves were collapsed to improve data resolution of both the shallow and deep reflection events. The reprocessing activities generally increased the illuminating strength of the TRV 434 marine seismic data to image the subsurface of the surveyed part of Taranaki Basin, which presented complex subsurface geology in terms of structures and rock association. Keywords: Kirchhoff migration; Omsby-Bandpass filters; Swell noise; Taranaki Basin; Velocity analysis. DOI 10.35180/gse-2020-0035